2019
DOI: 10.7197/cmj.vi.590598
|View full text |Cite
|
Sign up to set email alerts
|

A field research for the determination the influence of physicians’ professionalism understanding on medical errors attitude

Abstract: To determine the influence of hospital-based physicians' attitudes toward medical errors on professionalism understanding Method: The research was carried out in a descriptive, cross-sectional, and interrogative design. The study was carried out at the Cumhuriyet University Hospital with 182 physicians. A survey form was used to collect data. The Cronbach alpha coefficient was calculated to be .809. Results: It was found that physicians' attitudes toward professionalism (x̄ = 3.72) and their attitudes towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In a study carried out in our country in which the same scale was used [18], it was indicated that physicians and nurses' mean medical error attitude averages were identical, and their awareness levels towards medical errors were positive. In the other two studies, physicians' total medical error attitude scores were interpreted as positive, with the mean of 3.69 [19] and 3.46 [20], similar to our study. In this study, only nurses' attitudes towards medical errors were investigated and it was found that nurses were quite aware of the importance of medical errors and error reporting.…”
Section: Resultssupporting
confidence: 87%
“…In a study carried out in our country in which the same scale was used [18], it was indicated that physicians and nurses' mean medical error attitude averages were identical, and their awareness levels towards medical errors were positive. In the other two studies, physicians' total medical error attitude scores were interpreted as positive, with the mean of 3.69 [19] and 3.46 [20], similar to our study. In this study, only nurses' attitudes towards medical errors were investigated and it was found that nurses were quite aware of the importance of medical errors and error reporting.…”
Section: Resultssupporting
confidence: 87%